2008
DOI: 10.1007/s11258-008-9483-1
|View full text |Cite
|
Sign up to set email alerts
|

Grass (Poaceae) richness patterns across China’s nature reserves

Abstract: Explaining grass richness patterns over broad geographic scales is a central issue of biogeography and macroecology. In this investigation, we document the richness patterns of grasses across China's nature reserves, and discuss their possible explanations at national and regional scales using grass richness data coupled with information from climatic and topographical variables. Our results suggest that the water-and energy-related variables and elevation range (a surrogate of topographical heterogeneity) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Legume (Fabaceae) and grass (Poaceae) are the two most functionally important plant groups on the globe (Croser et al, 2006 ; Liu et al, 2009 ). In agroecosystems, legume, and grass normally occur as food crops, vegetables, forages, cover crops, and weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Legume (Fabaceae) and grass (Poaceae) are the two most functionally important plant groups on the globe (Croser et al, 2006 ; Liu et al, 2009 ). In agroecosystems, legume, and grass normally occur as food crops, vegetables, forages, cover crops, and weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Altitudinal range is widely used as a proxy of habitat heterogeneity to explain spatial patterns of species diversity [6][7][8] . Most of the relevant studies showed that altitudinal range positively and significantly correlated with species diversity [9][10] , as wide altitudinal range could provide mosaics and gradients for critical resources, such as ambient energy availability, precipitation or micro-habitat affecting co-existing species, thereby leading to higher biodiversity [10] .…”
Section: Introductionmentioning
confidence: 99%